Anaerobic acidification of cheese-whey in the MBBR reactor - Lanko, Iryna (2013)
In this study cheese-whey conversion into VFAs as a source for biopolymers production was investigated. Cheese-whey was chosen due to its high organic content being a by-product from the cheese production factory, as a part of valorisation methodology for industrial waste streams. Cheese-whey acidification process was used as an alternative to the waste treatment technologies. To study the acidification of cheese-whey, a set of experiments was carried out to produce short-chain volatile fatty acids (VFAs), in order to find out its ratio to the total chemical oxygen demand (tCOD) of feed present in the reactor. The proportional amounts of Acetic, Propionic and i-Butyric acids towards the rest of the VFAs were also important in order to evaluate the MBBR efficiency for different operational parameters such as hydraulic retention time (HRT), alkalinity and organic load rate applied (OLR). To fulfil these goals the mass balances of the system were performed. The maximum production rates of Acetic, Propionic and i-Butyric acids associated with simultaneous changes in OLR and alkalinity at a constant HRT of 12 h, were investigated (70% and 65% of total VFAs produced – at Phases 0 and 4, respectively). The degree of acidification of cheese-whey to the short-chain VFAs was about 33% and 27% of the influent COD concentration, at Phases 0 and 4, respectively. The optimum operational conditions under study where the maximum production rates of Acetic, Propionic and i-Butyric acids occurred were at an alkalinity of 3.6 gCaCO3/L and an OLR = 35 gCOD/L*d (Phase 4). At this optimum conditions for acids production, the average rate of COD removal was equal to 20% and the rate of methane production was equal to zero.